Application of DNP-enhanced solid-state NMR to studies of amyloid-β peptide interaction with lipid membranes. (May 2021) - Deo, Thomas; Cheng, Qinghui; Paul, Subhadip; Qiang, Wei; Potapov, Alexey
Abstract: The cellular membrane disruption induced by the aggregation of Aβ peptide has been proposed as a plausible cause of neuronal cell death during Alzheimer's disease. The molecular-level details of the Aβ interaction with cellular membranes were previously probed using solid state NMR (ssNMR), however, due to the limited sensitivity of the latter, studies were limited to samples with high Aβ-to-lipid ratio. The dynamic nuclear polarization (DNP) is a technique for increasing the sensitivity of NMR. In this work we demonstrate the feasibility of DNP-enhanced ssNMR studies of Aβ40 peptide interacting with various model liposomes: (1) a mixture of zwitterionic 1-palmitoyl-2-oleoyl-glycero-3-phosphocholine (POPC) and negatively charged 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1'-rac-glycerol) (POPG); (2) a mixture of POPC, POPG, cholesterol, sphingomyelin and ganglioside GM1; (3) the synaptic plasma membrane vesicles (SPMVs) extracted from rat brain tissues. In addition, DNP-ssNMR was applied to capturing changes in Aβ40 conformation taking place upon the peptide insertion into POPG liposomes. The signal enhancements under conditions of DNP allow carrying out informative 2D ssNMR experiments with about 0.25 mg of Aβ40 peptides (i.e. reaching Aβ40 -to-lipid ratio of 1:200). In the studied liposome models, the 13 C NMR chemical shifts at many 13 C-labelled sites of Aβ40 are characteristic of β-sheets. In addition, in POPG liposomes the peptide forms hydrophobic contacts F19-L34 and F19-I32. Both the chemical shifts and hydrophobic contacts of Aβ40 in POPG remain the same before and after 8 h of incubation. This suggests that conformation at the 13 C-labelled sites of the peptide is similar before and after the insertion process. Overall, our results demonstrate that DNP helps to overcome the sensitivity limitation of ssNMR, and thereby expand the applicability of ssNMR for charactering the Aβ peptide interacting with lipids.